Pembelajaran Learning Cycle 5e berbantuan Geogebra terhadap Kemampuan Pemahaman Konsep Matematis - Pratiwi, Dona Dinda (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
The purpose of this study was to find out whether there was an influence of Geogebra's 5E Learning Cycle learning model on understanding mathematical concepts. This type of research is a quasi-experimental research, data analysis techniques in this study using the NGain test and T test. Based on the calculation obtained the average value of NGain in the experimental class is 0.686 and the average value of N-Gain in the control class is 0.354. The conclusion that can be drawn from these calculations is that there is an increase in the ability to understand the mathematical concepts of students in the Geogebra-assisted 5E Learning Cycle class in the learning process, this also shows that the geogebra application has a positive influence on improving the ability to understand mathematical concepts in the learning process.